2019
DOI: 10.15640/jaes.v8n1a10
|View full text |Cite
|
Sign up to set email alerts
|

Breaking seed dormancy in Philenoptera violacea (Klotzsch) Schrire using different pre-sowing treatment methods

Abstract: Seeds of many woody plant species cannot germinate even if they are sown under optimal moisture, oxygen and soil conditions because of hard seed coat dormancy. A seed germination experiment to evaluate the suitability of various dormancy breaking methods in Philenoptera violacea seeds was conducted in the laboratory of the Department of Crop Science and Production, Botswana University of Agriculture and Natural Resources (BUAN) between November and December 2017. A completely randomized design (CRD) with 10 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The present study confirms results from earlier seed germination studies on other leguminous species, e.g. species of Acacia (Larsen, 1964;Clemens et al, 1977;Bebawi and Mohamed, 1985;Sniezko and Gwaze, 1987;Danthu et al, 1992;Masamba, 1994;Teketay, 1996a;Tadros et al, 2011), Afzelia and Baikiaea (Botsheleng, et al, 2014), Albizia (Babeley et al, 1986;Msanga and Maghembe, 1986;Khan and Tripathi, 1987;Teketay et al, 1996a, Cadaba (Teketay, 1996a), Caesalpinia (Ngulube, 1989;Teketay, 1996a), Erythrina (Teketay, 1994) and Leucaena (Oakes, 1984;Babeley and Kandaya, 1985;Duguma et al, 1988;Teketay, 1996a;Tadros et al, 2011), Calliandra and Sesbania (Albrecht, 1993), Entada, Delonix and Prosopis (Teketay, 1996a), Faidherbia (Fredrick et al, 2016), Vachellia and Peltophorum (Mojeremane et al, 2017;Mojeremane et al, 2018;Kahaka et al, 2018;Odirile et al, 2019), Dicrostachys and Senegalia (Kahaka et al, 2018), and Philenoptera (Setlhabetsi et al, 2019), which demonstrated that scarification of seeds through mechanical, sulphuric acid and boiling water pre-sowing treatments improved germination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study confirms results from earlier seed germination studies on other leguminous species, e.g. species of Acacia (Larsen, 1964;Clemens et al, 1977;Bebawi and Mohamed, 1985;Sniezko and Gwaze, 1987;Danthu et al, 1992;Masamba, 1994;Teketay, 1996a;Tadros et al, 2011), Afzelia and Baikiaea (Botsheleng, et al, 2014), Albizia (Babeley et al, 1986;Msanga and Maghembe, 1986;Khan and Tripathi, 1987;Teketay et al, 1996a, Cadaba (Teketay, 1996a), Caesalpinia (Ngulube, 1989;Teketay, 1996a), Erythrina (Teketay, 1994) and Leucaena (Oakes, 1984;Babeley and Kandaya, 1985;Duguma et al, 1988;Teketay, 1996a;Tadros et al, 2011), Calliandra and Sesbania (Albrecht, 1993), Entada, Delonix and Prosopis (Teketay, 1996a), Faidherbia (Fredrick et al, 2016), Vachellia and Peltophorum (Mojeremane et al, 2017;Mojeremane et al, 2018;Kahaka et al, 2018;Odirile et al, 2019), Dicrostachys and Senegalia (Kahaka et al, 2018), and Philenoptera (Setlhabetsi et al, 2019), which demonstrated that scarification of seeds through mechanical, sulphuric acid and boiling water pre-sowing treatments improved germination.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to obtain rapid, uniform and high germination, the dormancy imposed by the hard seed coat should be removed. Lack of knowledge of the germination requirements of leguminous species is an obstacle for their successful artificial regeneration (Teketay, 1996a, b;Mojeremane et al, 2017Mojeremane et al, , 2018Odirile et al, 2019;Setlhabetsi et al, 2019). Different scarification techniques, such as mechanical, acid and boiling/hot water scarification have been widely used (Teketay, 1996a(Teketay, , b, 1998(Teketay, , 2005Aref et al, 2011;Tadros et al, 2011;Missanjo et al, 2014;Rasebeka et al, 2014;Fredrick et al, 2016) because they can improve germination by overcoming seed dormancy within a relatively short period of time (Tadros et al, 2011;Mojeremane et al, 2017;Odirile et al, 2019;Setlhabetsi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Before the ANOVA, the germination percentage data were arcsine transformed to meet the requirement of normality. 20 Significant differences of means were tested using Tukey's Honestly Significant Difference (HSD) at the significance level of P < 0.05.…”
Section: Data Analysesmentioning
confidence: 99%
“…Hard seed coat-imposed dormancy of leguminous species hinders their successful artificial regeneration (Teketay, 1996a, b;Mojeremane et al, 2017Mojeremane et al, , 2018Odirile et al, 2019;Setlhabetsi et al, 2019). Several presowing treatments have been used to enhance germination of seeds characterised by hard coats.…”
Section: Introductionmentioning
confidence: 99%
“…These include mechanical, acid, cold, hot and boiling water scarification (Teketay, 1996a(Teketay, , b, 1998(Teketay, , 2005Alamgir and Hossain, 2005;Amri, 2010;Azad et al, 2011;Rasebeka et al, 2014;Fredrick et al, 2017;Kahaka et al, 2018;Opoku et al, 2018;Botumile et al, 2020), among others. These techniques can improve germination by overcoming seed dormancy within a relatively short period of time (Tadros et al, 2011;Mojeremane et al, 2017Mojeremane et al, , 2018Odirile et al, 2019;Setlhabetsi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%